2019
DOI: 10.1002/jor.24237
|View full text |Cite
|
Sign up to set email alerts
|

Alignment differs between patellofemoral osteoarthritis cases and matched controls: An upright 3D MRI study

Abstract: Patellofemoral (PF) osteoarthritis (OA) is a prevalent and clinically important knee OA subgroup. Malalignment may be an important risk factor for PF OA. However, little is known about alignment in PF OA, particularly in an upright, weightbearing environment. Using a vertically‐oriented open‐bore MR scanner, we evaluated 3D knee alignment in 15 PF OA cases and 15 individually matched asymptomatic controls. We imaged one knee per participant while they stood two‐legged at four flexion angles (0°, 15°, 30°, 45°)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“… 49 , 50 On the other hand, Collins et al 14 found radiographic and MRI-defined PFOA in 20% to 30% of patients aged 26 to 50 years with persistent PFP. Increasing evidence suggests that morphological abnormalities are related to the differences in alignment between patients with PFOA and controls, 30 , 31 , 35 particularly when the features of patella alta, lateral patellar displacement, and increased lateral patellar tilt are present. 52 Although PFJ malalignment appears to induce increased contact pressure and cartilage shear stress, the mechanism by which an increased joint load contributes to PFP is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 On the other hand, Collins et al 14 found radiographic and MRI-defined PFOA in 20% to 30% of patients aged 26 to 50 years with persistent PFP. Increasing evidence suggests that morphological abnormalities are related to the differences in alignment between patients with PFOA and controls, 30 , 31 , 35 particularly when the features of patella alta, lateral patellar displacement, and increased lateral patellar tilt are present. 52 Although PFJ malalignment appears to induce increased contact pressure and cartilage shear stress, the mechanism by which an increased joint load contributes to PFP is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…controls [20][21][22] With the exception of hip strength 12 13 no two studies have yet to evaluate the same clinical features (physical exam, strength, ROM, functional performance), and no study has yet reported on a spectrum of clinical features together in one sample, or associations among such features. A more complete clinical picture of patellofemoral OA would inform clinical research aimed ultimately at primary and secondary knee OA prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This criteria for selecting patients provides a focus on a specific type of arthritis. We believe that patients with isolated patellofemoral arthritis have different patellofemoral biomechanics 2 thus should be assessed separately.…”
Section: Discussionmentioning
confidence: 99%
“…1 The aetiology is unclear but the altered biomechanics at the patellofemoral joint is believed to be the main cause of progressive patellofemoral degeneration and eventually established patellofemoral osteoarthritis. 2 Severe isolated patellofemoral arthritis can be treated with total knee replacement. [3][4][5][6][7][8] Total knee replacement in general gives a good result but some patients continue to suffer from pain, patellofemoral crepitus and reduced range of movements, which limit their function.…”
Section: Introductionmentioning
confidence: 99%